2019
DOI: 10.1088/1361-648x/ab111c
|View full text |Cite
|
Sign up to set email alerts
|

First-principles DFT insights into the structural, elastic, and optoelectronic properties ofαandβ-ZnP2: implications for photovoltaic applications

Abstract: Binary II-V semiconductors are highly optically active materials, possess high intrinsic mechanical and chemical durability, and have electronic properties ideal for optoelectronic applications. Among them, zinc diphosphide (ZnP 2) is a promising earth-abundant absorber material for solar energy conversion. We have investigated the structural, mechanical, and optoelectronic properties of both the tetragonal (α) and monoclinic (β) phases of ZnP 2 using standard, Hubbard-corrected and screened hybrid density fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The lattice was optimized until residual forces on atoms in their equilibrium positions not exceeded 5 meV Å −1 . The results of this optimization are summarized in table 1. In agreement with earlier theoretical studies [7], both ZnP 2 and CdP 2 clearly shown a non-metallic behaviour. This Table 1.…”
Section: Crystallographic Structure Of Znp 2 and Cdp 2 And Computatio...supporting
confidence: 92%
See 2 more Smart Citations
“…The lattice was optimized until residual forces on atoms in their equilibrium positions not exceeded 5 meV Å −1 . The results of this optimization are summarized in table 1. In agreement with earlier theoretical studies [7], both ZnP 2 and CdP 2 clearly shown a non-metallic behaviour. This Table 1.…”
Section: Crystallographic Structure Of Znp 2 and Cdp 2 And Computatio...supporting
confidence: 92%
“…Metal atoms and phosphorous occupy general position (8b) within the unit cell. Experimentally determined lattice parameters are a = b = 0.50586 (7) nm and c = 1.8506(4) nm for ZnP 2 and a = b = 0.52768 (7) nm and c = 1.9753(3) nm for CdP 2 [6]. Table 1 summarizes experimental and DFT-calculated, as is described below, positions of atoms within ZnP 2 unit cell.…”
Section: Crystallographic Structure Of Znp 2 and Cdp 2 And Computatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…The valence band of β-ZnP2 is found to be dominated by the electronic states of the Zn-pd and P-p orbitals, whereas the conduction band is composed mainly of the Zn-d orbitals. 24 The relaxed bulk β-ZnP2 structure was employed to create the seven low-Miller index surfaces -(001), ( 010), ( 100), ( 011), ( 101), ( 110) and (111) and considering all possible non-dipolar terminations. Each surface was fully relaxed to predict the lowest-energy structures, surface energies, and order of stability.…”
Section: Bulk and Surface Characterisation Of β-Znp2mentioning
confidence: 99%
“…23 In our recent study, we have employed the screened hybrid approach to determine the optoelectronic and dielectric properties of the α-ZnP2 and β-ZnP2 phases, and predicted a thin-film PV absorbing efficiency of almost 10% for β-ZnP2. 24 As surfaces and interfaces play an important role in the rational design of tandem solar cells, it is important to gain an atomic-level understanding of their structures and composition, whereas the relative stabilities of β-ZnP2 surfaces and possible changes in their electronic structures and crystal morphology upon prolonged exposure to wet conditions should also be elucidated for practical applications. Low surface stability in the presence of moisture and oxygen [10][11] remains a major problem that severely limits commercial fabrication of efficient zinc-based PV materials.…”
Section: Introductionmentioning
confidence: 99%